Beyond Dealumination: Does Fluorine Reshape Zeolitic Acidity? - Lu Song; Natalia Morlanés; Edy Abou−Hamad; Javier Ruiz-Martínez (Journal of the American Chemical Society, 2026)
Abstract Fluoride-containing media have been widely adopted in the post-treatment of ZSM-5 zeolites for heterogeneous catalysis. Their effects have predominantly been discussed in terms of the well-established dealumination process. However, comparatively little attention has been paid to the influence of residual fluorine on the local chemical environment, which governs zeolitic acidity and catalytic performance. In this work, mild fluorination of ZSM-5 was achieved by controlling the ammonium fluoride (NH4F) content during hydrothermal treatment. Our findings reveal that fluorine induces significant perturbations in the acidic properties of ZSM-5, distinct from the conventional dealumination effect. To elucidate these effects at the atomic level, we employed 27Al, 19F, 27Si, and 1H solid-state magic angle spinning (MAS) nuclear magnetic resonance (NMR) spectroscopy, which provided detailed chemical and structural insights. The correlated incorporation of fluorine within the zeolite framework leads to strong local polarization, thereby enabling the protons to exhibit Brønsted acid site (BAS)-like behavior. Comparative analysis with nonaluminum-containing silicalite-1 further confirmed the fluorine-induced acidity, as supported by two-dimensional (2D) 1H double-quantum single-quantum (DQ–SQ) MAS NMR results. Catalytic testing in the methanol-to-hydrocarbon (MTH) reaction demonstrated that such fluorinated ZSM-5 exhibits an extended catalytic lifetime along with enhanced aromatic selectivity, underscoring the pivotal electronic influence of fluorine beyond its classic role in dealumination.